RANCANG BANGUN SISTEM INFORMASI PENJUALAN MENGGUNAKAN METODE WATERFALL - Candra Budi Susila Candra Budi Susila; Miftahul Huda Huda (Universitas Islam Balitar Blitar, 2021)
Abstract - esign and Design of Computer Sales Information Systems using the waterfall method is a study that aims to design and build sales information systems at a computer retail store or